A Comparative Study: Void Formation in Silicon Wafer Direct Bonding by Oxygen Plasma Activation with and without Fluorine. (1st January 2017) - Wang, Chenxi; Liu, Yannan; Suga, Tadatomo
Abstract : A quantitative evaluation of void formation in plasma activated bonding of 200-mm silicon wafers is demonstrated. As a comparison, the wafers were treated with oxygen plasma or fluorine containing oxygen plasma prior to bonding, respectively. The bonding was performed at the room temperature (∼25°C), and all the bonded pairs were annealed from 200 to 800°C. Results shows adding a small amount of fluorine into the oxygen plasma could decrease the hydrophilicity of the silicon surfaces, and effectively mitigate void formation at the bonding interfaces during the subsequent annealing process. Moreover, long plasma treatments (e.g. >60 s) may produce more porous surfaces resulting in more annealing voids. A short fluorine containing plasma treatment (e.g. ∼10 s) is able to remove organic contaminants efficiently and causes restricted hydrophilic surfaces with less subsurface damages. It may lead to much fewer voids at bonding interfaces during the annealing. Void formation models are proposed to gain insight the mechanism of the plasma activated bonding without and with fluorine, respectively.